PUBLIC FUNDING AND SELFEMPLOYMENT CREATION (Revista Lusófona de Economia e Gestão das Organizações, 2017)
When countries are in times of limited financial resources the provision of public funds to active labour market policies should receive close attention from the governments and become as effective as possible. This aim should be always grounded in evidence criteria and not in political insights or ideological social constructions.This paper aims to provide some data and potential conclusions in order to deliver a modest contribution to the evidence-based debate on ALMP policy making in Portugal.The analysis was made over two variables: the public expenditure on self-employment creation measures and the number of self-employment positions created. The results suggest that there is a weak linear correlation between the two variables. This might point to an inefficiency in the use of public funds; or in other hand, it may mean that public expenditure is only remotely responsible for the creation of self-employment positions and, therefore, that there are other variables (or reasons) that explain the phenomenon.